2022
DOI: 10.1039/d2an00862a
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi-material portable 3D-printed platform for electrochemical detection of dopamine and glucose

Abstract: Design and production of a one-step 3D-printed functional electrochemical biosensor for efficient detection of dopamine and glucose in low-volume samples (100 μL). Glucose detection via ruthenium-mediated amperometry provides results in 60 seconds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The limit of detection (LOD) was 0.8 μM for the 30% infill electrode ( n = 6), while this was marginally lower at 0.6 μM for the 100% infill electrode. These responses are comparable to other studies which have measured dopamine on graphene/PLA and CB/PLA electrodes . The LOD and sensitivity for the determination of dopamine on the 30% infill electrode were identical to those observed on the 100% electrodes.…”
Section: Resultssupporting
confidence: 87%
“…The limit of detection (LOD) was 0.8 μM for the 30% infill electrode ( n = 6), while this was marginally lower at 0.6 μM for the 100% infill electrode. These responses are comparable to other studies which have measured dopamine on graphene/PLA and CB/PLA electrodes . The LOD and sensitivity for the determination of dopamine on the 30% infill electrode were identical to those observed on the 100% electrodes.…”
Section: Resultssupporting
confidence: 87%
“…This was achieved by designing a reservoir‐type structure, a subsided oval‐shaped portion in the device around the three electrodes of a depth of 200 μm. The combined effect of the subsided well design [ 29 ] and hydrophobic nature of resin permitted sample quantities as low as 5 μL and as high as 40 μL to be retained on the device, as shown in Figure S3a–h, Supporting Information, with spillage beginning to occur beyond this point, as depicted in Figure S3i, Supporting Information, when ≈45 μL of sample was added.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28] It may not be as versatile as a multifunctional device, but it excels in sensing applications, making it appropriate for situations when specialized sensor capabilities are needed. [29][30][31][32] The smart 3D printed mask aims to achieve the former by mitigating the time and complexity factor as much as possible and demonstrating how it can also perform specialized sensing.…”
mentioning
confidence: 99%
“…Multi-material 3D-printed sensors were produced as previously described (Domingo-Roca et al, 2022). Briefly, a portable electrochemical biosensor including reference, counter, and working electrodes was 3D-printed in a RAISE3D-E2 IDEX Dual 3D printer (nozzle diameter 0.4 mm) using polylactic acid (PLA, RAISE) as main housing, and carbon black PLA (CB-PLA, ProtoPasta) for the electrodes.…”
Section: D-printingmentioning
confidence: 99%
“…Our previous work demonstrated that (i) functionalisation of SPEs through gel modification improves the measurement duration and can detect a range of microorganisms (Hannah et al, 2019(Hannah et al, , 2020b, and (ii) it is possible to exploit multi-material 3D-printing to produce one-step, portable electrochemical devices to reliably detect a series of redox analytes and life-relevant molecules such as dopamine and glucose (Domingo-Roca et al, 2022). In this work, we combine these two concepts into a novel and rapid approach to antimicrobial susceptibility testing (AST) determination via an impedimetric biosensor.…”
Section: Introductionmentioning
confidence: 99%